TRADITIONAL REPRESENTATION OF WOMEN IN INDONESIAN AND ENGLISH FOLKTALES - Surya Darmadali, Waode (JURNAL SIPAKALEBBI, 2022)
In Toraja, Indonesia and England folktales bring important impact to the community. In Indonesia, a folktale is used as a medium of entertainment as well as a teaching tool for children. These folktales are told by grandparents, mother, father, or uncles to their children or grandchildren with the aims to educate, tell the histories, and give the information about the origin of the names and places. This study aims to understand how the similarity and differences between the main characters in Torajanese and English folktales. Furthermore, the research also studies how the traditional representation of women in Indonesia and English folktales. This study uses a qualitative method that refers more to narrative. With regard to data, this research, which is an area of literary study, refers to narrative events in a story that contain events that are described by words, phrases, sentences, and involve characters and settings. Based on the results of our research, we argue that many female characters in Eastern Indonesian folktales and English folktales are subject to objectification. The objectification of female figures is carried out in the form of women as objects of sexuality, women as a medium of exchange of power, and women being passive and working in the domestic sphere. This finding shows that the folktale of Eastern Indonesia cannot be separated from patriarchal ideology. These stories show that women in the imagination of the Indonesian people still occupy an inferior position compared to men. Furthermore, the female characters also experience objectification and inequality as in folktales from Western Indonesia.